Anthroponymic Analysis of The Kayu Agung Village Community, Mepanga Subdistrict: An Onomastic Study - Sri Yunita; Syamsuddin Syamsuddin; Mardiah Mardiah (Applied Linguistics: Innovative Approaches and Emerging Trends, 2026)
Abstrak This study aims to describe the anthroponymic forms of the Kayu Agung Village community, Mepanga Subdistrict, and the underlying factors of personal naming based on an onomastic study. Previous anthroponymic studies have predominantly focused on Javanese society and urban areas, while transmigration village communities like Kayu Agung remain under-researched; thus, this study aims to fill that gap. This research employs a qualitative descriptive method, utilizing a data source of 50 community personal names and their naming backgrounds, supported by secondary data from village documents and related literature. Data were collected through observation, interviews, listening, recording, note-taking, and documentation techniques, then analyzed using the Miles and Huberman interactive model, which includes data reduction, data display, and conclusion drawing. The results show that the anthroponymic forms of the Kayu Agung community consist of word forms (single words and phrases), language of origin (Javanese, Buginese, Arabic, Indonesian), and lexical forms containing meanings of identity, hopes, and cultural values. The underlying factors for naming include hopes and prayers, family history, and modernization. It can be concluded that the naming system of the Kayu Agung community is not merely about identity, but rather a reflection of cultural values passed down across generations, while simultaneously experiencing shifts due to changing times, education, and religion.